Proceedings of the 3rd International Conference on Banking, Accounting, Management and Economics (ICOBAME 2020) 2020
DOI: 10.2991/aebmr.k.210311.084
|View full text |Cite
|
Sign up to set email alerts
|

Profitability, Liquidity, Size, Reputation of Public Accounting and Timeliness Reporting Financial Statement: An Analysis of Manufacturing Company Overview in Indonesia

Abstract: This study aims to find empirical evidence about the factors that affect the timely delivery of the financial statement of manufacturing companies listed on profitability, liquidity, size, and the reputation of the public accounting firm on the timelines of financial statements. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange. The sampling method uses purposing sampling with the study period of 2015 to 2018 and obtained as many as 568 companies. The data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Prior literature relates audit firm reputation with the audit firm size (Badawy and Zaki, 2023;DeAnglo, 1981). In the same context, according to the signaling theory, choosing high quality auditors, such as Big 4 audit firms, will send a good signal to the market and stakeholders (Sunarto et al, 2021). Because a good audit firm reputation is related to high audit quality, investors and other stakeholders will have more trust in the company's financial performance and position (Badawy and Zaki, 2023).…”
Section: Audit Firm Reputationmentioning
confidence: 99%
“…Prior literature relates audit firm reputation with the audit firm size (Badawy and Zaki, 2023;DeAnglo, 1981). In the same context, according to the signaling theory, choosing high quality auditors, such as Big 4 audit firms, will send a good signal to the market and stakeholders (Sunarto et al, 2021). Because a good audit firm reputation is related to high audit quality, investors and other stakeholders will have more trust in the company's financial performance and position (Badawy and Zaki, 2023).…”
Section: Audit Firm Reputationmentioning
confidence: 99%
“…The theory is also explained by the fact that a party provides information from enterprises to emit signals about financial information to users (Akerlof, 1970). It is an opportunity to create an advantage and brand for their business activities compared to other enterprises so that information user can better understand the business situation of enterprises (Sunarto et al, 2020). The theory is applied to test the influence of the characteristics of the firm on TID.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study concluded that profitability is the most significant company specific determinant of Audit Report Lag. Sunarto et al (2020) concluded that large firms use reputable audit firms that they perform audits more efficiently so they will produce fairness information in their financial statements. Dewi et al (2019), while employing signaling theory, examined and analyzed the association between audit tenure and financial distress on delay in publication of financial statement in Indonesia.…”
Section: Signaling Theorymentioning
confidence: 99%
“…Studies by Alfraih (2016); Ohaka and Akani (2017); Adediran et al, (2019); Borgi et al (2021);Ferdayani et al, (2019); Dewi et al ( 2019); Savitri et al (2019);Sunarto et al, (2020); Wibowo and Saleh (2020); Borgi et al (2021) had conceptual gaps. In addition, all the mentioned studies did not establish the effect of bankruptcy risk indicators on financial reporting timeliness of listed companies in Kenya.…”
Section: Conceptual Gapsmentioning
confidence: 99%
See 1 more Smart Citation